Overexpression of PtDXS Enhances Stress Resistance in Poplars - Wei, Hui (Int J Mol Sci, 2019)
1-Deoxy-d-xylulose-5-phosphate synthase (DXS) is the rate-limiting enzyme in the plastidial methylerythritol phosphate pathway (MEP). In this study, PtDXS (XM_024607716.1) was isolated from Populus trichocarpa. A bioinformatics analysis revealed that PtDXS had high homology with the DXSs of other plant species. PtDXS expression differed among plant tissues and was highest in young leaves and lowest in roots. The recombinant protein was produced in Escherichia coli BL21 (DE3), purified, and its activity evaluated. The purified protein was capable of catalyzing the formation of 1-deoxy-d-xylulose-5-phosphate (DXP) from glyceraldehyde-3-phosphate and pyruvate. A functional color assay in E. coli harboring pAC-BETA indicated that PtDXS encodes a functional protein involved in the biosynthesis of isoprenoid precursors. The treatment of P. trichocarpa seedlings with 200 μM abscisic acid (ABA), 200 mM NaCl, 10% polyethylene glycol(6000), and 2 mM H(2)O(2) resulted in increased expression of PtDXS. The ABA and gibberellic acid contents of the transgenic lines (Poplar Nanlin 895) were higher than wild types, suggesting that DXS is important in terpenoid biosynthesis. Overexpression of PtDXS enhanced resistance to S. populiperda infection. Furthermore, the transgenic lines showed decreased feeding by Micromelalopha troglodyta, supporting the notion that PtDXS is a key enzyme in terpenoid biosynthesis.